(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
Extreme weather and climate conditions pose significant challenges to the durability and performance of asphalt pavements, accelerating distresses such as rutting, moisture damage, and cracking. To address these challenges, this study presents the development of a climate-resilient asphalt mixture enhanced with 4% Styrene-Butadiene-Styrene (SBS) polymer, 0.5% Amine-Based Anti-Stripping Agent (AD-here® LOF 65-00 EU), and 5% Tall Oil rejuvenator (Delta-S). Laboratory experiments, involving the Hamburg wheel-track test for rutting resistance and the strain-controlled four-point bending beam test for fatigue life (Nf) evaluation and revealed important enhancements over the unmodified control mix. The modified asphalt achieved a 55% decrease in rut depth at 20,000 passes and exhibited a 50% increase in initial stiffness, reaching 720 MPa at 200 µε and 700 MPa at 400 µε. In terms of fatigue performance, the mix sustained 120,000 cycles at 200 µε and 65,000 cycles at 400 µε, nearly tripling the durability compared to the control. Moreover, Artificial Neural Network (ANN) models were employed to predict rutting depth and fatigue life up to 100,000 passes and 600 µε, providing a reliable tool for performance forecasting under extreme climatic conditions. The findings reveal that the proposed amendment approach significantly enhances the structural integrity, moisture resistance, and long-term durability of asphalt pavements. This work not only bridges the gap between laboratory testing and practical implementation, but additionally establishes a new benchmark for resilient and sustainable pavement design in challenging environments by promoting longer service life and reducing maintenance needs, leading to minimizing resource consumption.